Giant thymoma successfully resected via hemiclamshell thoracotomy: a case report - Zhao, Weigang; Fang, Wentao (Journal of Thoracic Disease, 2016)
Thymoma is an epithelial neoplasm of the thymus. It commonly lies in the anterior mediastinum and represents 20–30% of mediastinal tumours in adults. In this report we present a case of giant thymoma locating in the anterior-inferior mediastinum. A 46-year-old male came to our institute with slight pectoralgia and dyspnea. Chest CT shows a giant tumor measuring 19 cm × 16 cm × 15 cm in the left thoracic cavity. After careful examination, we performed surgery. At surgery, we found the tumor was adherent to left upper lobe of the lung, mediastinal pleura, and parietal pleural. The tumor was completely resected with combined resection of part left upper lobe of lung. The weight of the tumor was 2,135 g. Pathological diagnosis indicated a type AB thymoma according to the World Health Organization classification and a diagnosis of Masaoka stage IIB was made.